AN ANALYTICAL STUDY OF THE LEGAL FRAMEWORK GOVERNING NFTS IN INDIA - Vikram; Sharma, Dr. Sangeeta (ShodhKosh: Journal of Visual and Performing Arts, 2024)
Non-Fungible Tokens (NFTs) have emerged as a significant innovation in the digital economy, particularly in India, where the intersection of art, technology, and finance is evolving rapidly. NFTs are unique digital tokens secured through blockchain technology, representing ownership of digital or physical assets such as art, music, collectibles, and virtual real estate. Their rise in India is marked by increasing participation from creators, investors, and technology platforms. Despite their growing popularity, NFTs operate within a fragmented and ambiguous legal environment. India currently lacks specific legislation dedicated to NFTs, leading to reliance on existing laws such as the Indian Contract Act, 1872; the Information Technology (IT) Act, 2000; intellectual property laws; and provisions in the Finance Act, 2022 concerning virtual digital assets. However, these frameworks offer limited clarity on issues such as copyright ownership, contract enforceability via smart contracts, taxation, and consumer protection. This research paper undertakes a comprehensive examination of the legal standing of NFTs in India. It evaluates the applicability of current legal instruments, identifies regulatory and operational gaps, and explores international best practices. The study also emphasizes the need for a clear, forward-looking legal framework that fosters innovation while ensuring adequate safeguards against fraud, misuse, and environmental concerns. A balanced regulatory approach is essential for India to harness the full potential of NFTs and position itself as a leader in the digital asset economy.